Internationalization and firm performance in Chindia countries: a meta-analytic review (2016)
For more than four decades, researchers have examined theoretically and empirically the relationship between internationalization and firm performance. While existing studies have provided important contributions, the stream of research still lacks consistency due to ambiguous findings on the internationalization-firm performance relationship. Moreover, previous research has often been limited to developed countries. The present study focuses on the emerging Chindia countries and determines the direction and the strength of the internationalization-firm performance relationship. Additionally, we have identified moderators of the relationship. Drawing on 21 studies, based on 9026 firms, we utilize a meta-analytic review to assess our hypotheses. Our results show that there is a significant and positive internationalization-firm performance relationship in Chindia countries. The effect of internationalization in India and China does not significantly differ. Moreover, we find that the effect of internationalization is significantly stronger in the United States as compared to the Chindia countries. The time period of data collection did not play an important role as a moderator. The present study contributes to the International Business literature by examining how and to which extent internationalization influences firm performance and offers implications for theory and practice as well as recommendations for future research.